CAUSALITY RELATIONSHIP BETWEEN EXCHANGE RATE AND STOCK PRICE INDEX IN ASEAN-4 - Khoerunisa (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the causal relationship between the exchange rate and stock price index inASEAN-4 in 2012 to 2020. The four countries used in this study are countries in Southeast Asia which areincluded in the category of emerging market countries, namely Indonesia, Malaysia, thePhilippines, and Thailand. This study uses a quantitative method with a comparative causalapproach, through the technical analysis of Vector Autoregression (VAR) to determine whether or notthere is a causal relationship between the research variables. This study uses secondary data obtainedfrom publications from institutions. This study found that there is a one-way causality relationship anddoes not apply the opposite from the stock price index to the exchange rates in Indonesia, Malaysia, and thePhilippines in the long and short term. Meanwhile, there is a one-way relationship and does not applythe opposite from the exchange rate to the stock price index in Thailand in the long and short term.